Taking flight: unveiling ryanair plc´s role in Europe´s airline industry landscape - Sousa, Manuel Peres Vieira de (2023)
This report aims to reach a final valuation of Ryanair Holdings PLC. In this report, we present an overview of the company’s major value drivers, which will be used for the valuation of the company. This report also encompasses an overview of the commercial airline industry.